Improving Image Compression Using DWT (International Journal of Engineering and Computer Science, 2016)
— Image compression has become an important process in today’s world of information exchange. Image compression helps in effective utilization of high speed network resources.The discrete wavelet transform (DWT) is a technique for converting a signal into elementary frequency components. It is widely used in image compression. Here some functions for compression of both gray scale and color images with DWT and its implementation in MATLAB have been developed. The DWT is very similar to a Fourier series , but in many ways, is much more flexible and informative. It is a tool which breaks up data into different frequency components or sub bands and then studies each component with a resolution that is matched to its scale. Unlike the Fourier series, it can be used on non-stationary transient signals with excellent results.